2023
DOI: 10.1038/s41598-023-28429-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the transcriptome of developing native and iPSC-derived mouse retinae by single cell RNA sequencing

Abstract: We report the generation and analysis of single-cell RNA-Seq data (> 38,000 cells) from mouse native retinae and induced pluripotent stem cell (iPSC)-derived retinal organoids at four matched stages of development spanning the emergence of the major retinal cell types. We combine information from temporal sampling, visualization of 3D UMAP manifolds, pseudo-time and RNA velocity analyses, to show that iPSC-derived 3D retinal organoids broadly recapitulate the native developmental trajectories. However, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Preliminary studies have shown that embryonic stem cells can be directed to differentiate into lung progenitor cells. This study laid the foundation for the subsequent induction of more mature lung organoids 13 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Preliminary studies have shown that embryonic stem cells can be directed to differentiate into lung progenitor cells. This study laid the foundation for the subsequent induction of more mature lung organoids 13 …”
Section: Introductionmentioning
confidence: 94%
“…This study laid the foundation for the subsequent induction of more mature lung organoids. 13 As an animal model, porcine characteristics are closer to human than mice; however, there is no established lung organoid model in pigs. The normal process of lung development in vivo involves the progression from definitive endoderm and abdominal foregut endoderm to thyroid or lung development, which requires specific factors for lung specification.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pooling of datasets generated in different studies enabled cross-condition comparisons 1,2 , population-level analysis 3,4 , and revealed evolutionary relationships between individual cell types 5 . The selection of pre-clinical models, such as organoids and animals, and the characterization of their limitations likewise rely on comparison with human tissues [6][7][8][9][10][11][12][13][14] . Similarly, the selection of the optimal sequencing protocols requires a comparison of datasets generated with different protocols 15,16 .…”
Section: Introductionmentioning
confidence: 99%